BRAND IMAGE AS A MEDIATION OF ELECTRONIC WORD OF MOUTH ON PURCHASING INTENTION OF LANEIGE - Chikita Fatimasokasari Supradita; Surpiko Hapsoro Darpito; Dwi Hari Laksana (Universitas Dian Nuswantoro Semarang, 2020)
The purpose of the study was to know and analyze the role of brand image as a mediator of the impact of the Electronic Word of Mouth on purchasing intention of Laneige’s product. A sample of 100 respondents used a purposive sampling technique. The type of test used to analyze the data was the validity and reliability test. The data analysis technique used is path analysis. The results of the Electronic Word of Mouth study have a significant and positive effect on brand image and purchasing intention. The Brand image also has a significant and positive impact on purchasing intention and directly has a role as a mediator on the impact of Electronic Word of Mouth on purchasing intention of Laneige’s Product.Keywords: Electronic Word of Mouth; Brand Image; Purchasing Intention